Impact of socioeconomic status on psychological functioning in survivorship following breast cancer and reconstruction. Issue 9 (26th April 2020) - Le, Nicole K.; Gabrick, Kyle S.; Chouairi, Fouad; Mets, Elbert J.; Avraham, Tomer; Alperovich, Michael
Abstract: Socioeconomic status (SES) remains an important population health risk factor and impacts a patient's experience of care during breast cancer. This study explored the relationship between SES and quality of life and satisfaction in survivorship following breast cancer and reconstruction. All patients underwent breast reconstruction at a single academic center from 2013 to 2017. Patients completed the five quality of life and satisfaction domains of the BREAST‐Q, a validated patient‐reported outcome measure. Estimated home value using a web‐based real estate website was used to approximate a patient's socioeconomic status. Correlations were evaluated using Pearson's correlation methods, where appropriate, as well as analysis of covariance. Data were stratified for comparison utilizing t tests and linear regression models. Significance was defined as P  ≤ .05. Four hundred patients underwent 711 breast reconstructions during the study time period. Satisfaction with the breast ( P  = .038) and psychosocial well‐being ( P  = .012) had significant positive correlations with increasing socioeconomic status. When stratifying patients' socioeconomic status into thirds, the upper third had significantly higher psychosocial well‐being ( P  = .001), satisfaction with breasts ( P  = .010), and physical well‐being of the chest ( P  = .001) than the lower third. Significance persisted even after controlling for cancer stage, treatment, complications, and baseline comorbidities. Higher socioeconomic status is associated with greater satisfaction with breast reconstruction and psychosocial well‐being following breast cancer treatment. Providing added social, psychological, and emotional support networks may be beneficial long after the initial cancer treatment and reconstruction are complete. Patients of lower socioeconomic status may benefit from additional resources.